Effect of temperature and relative humidity on algae biofouling on different fired brick surfaces. (28th February 2019) - Quagliarini, Enrico; Gianangeli, Andrea; D'Orazio, Marco; Gregorini, Benedetta; Osimani, Andrea; Aquilanti, Lucia; Clementi, Francesca
Highlights: Microalgae biofouling on different porous and rough fired brick surfaces was studied. Its growth under different values of relative humidity and temperature was tested. At relative humidity lower than 98% no growth was present. Temperature influenced algae growth rate and covered area as a function of time. Biofouling experimental results were modelled by a modified Avrami's law. Abstract: The purpose of this study was to evaluate the effect of environmental temperature and relative humidity on algae biofouling that often occurs on porous and rough fired brick surfaces. Brick samples were chosen since their common use on building façades. Accelerated growth tests were performed under different relative humidities and different temperatures. Results showed the effects of different temperature conditions in terms of algae growth delay and reduction of the covered area. All the relative humidity conditions tested substantially showed no growth from an engineering standpoint. The modified Avrami's law succeeded in modelling the biofouling under the different environmental conditions.